2012
DOI: 10.3109/0142159x.2012.669084
|View full text |Cite
|
Sign up to set email alerts
|

Establishing faculty needs and priorities for peer-mentoring groups using a nominal group technique

Abstract: Peer-mentoring groups are purported to enhance faculty productivity and retention, but the literature about implementation is sparse. Nominal Group Sessions (n=5) with 66 faculty members in different tracks developed prioritized lists of unmet professional development needs and potential group activities. Common items included mentor relationships, research skills, informal peer discussions of successes and challenges, and professional skills workshops. Items particular to specific academic tracks included int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Our results suggest that new faculty benefit from group mentoring because it provides them a support system, helps them feel more a part of the larger institution community, and provides a safe place to share their struggles with their job demands. These findings validate reports by other investigators (Colon‐Emeric, Bowlby, & Svetkey, ; Carr, Bickel, & Inui, ; Paloli, Knight, Dennis, & Frankel, ). In addition, the mentees' evaluation surveys indicated that when they could not be matched up with a mentor of the same gender and/or ethnicity, they were able to get their psychosocial/personal needs met with their mentoring group.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that new faculty benefit from group mentoring because it provides them a support system, helps them feel more a part of the larger institution community, and provides a safe place to share their struggles with their job demands. These findings validate reports by other investigators (Colon‐Emeric, Bowlby, & Svetkey, ; Carr, Bickel, & Inui, ; Paloli, Knight, Dennis, & Frankel, ). In addition, the mentees' evaluation surveys indicated that when they could not be matched up with a mentor of the same gender and/or ethnicity, they were able to get their psychosocial/personal needs met with their mentoring group.…”
Section: Discussionsupporting
confidence: 92%
“…This model has potential benefits requiring fewer resources with the mentor and mentee usually being closer in personal and professional experiences, offering an opportunity for more understanding relationship 5. Peer mentoring has been established for medical students,6 7 in academic medicine8 and nursing 9.…”
Section: Introductionmentioning
confidence: 99%
“…The mentor and mentee are closer in terms of personal and professional experiences, enabling the peer-mentor to more closely empathize with the challenges faced by the mentee compared to classical mentoring arrangements (10). There is also greater potential for social interaction within the peer-mentor relationship, which in the context of training may increase the sense of community.…”
Section: Introductionmentioning
confidence: 99%